2012
DOI: 10.1371/journal.pone.0042724
|View full text |Cite
|
Sign up to set email alerts
|

Salmon Aquaculture and Antimicrobial Resistance in the Marine Environment

Abstract: Antimicrobials used in salmon aquaculture pass into the marine environment. This could have negative impacts on marine environmental biodiversity, and on terrestrial animal and human health as a result of selection for bacteria containing antimicrobial resistance genes. We therefore measured the numbers of culturable bacteria and antimicrobial-resistant bacteria in marine sediments in the Calbuco Archipelago, Chile, over 12-month period at a salmon aquaculture site approximately 20 m from a salmon farm and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
135
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 86 publications
1
135
1
12
Order By: Relevance
“…However, this greatly expands our knowledge of the diversity of genes responsible for these resistance patterns by linking resistance phenotypes to genotypes and identifying potential novel resistance genes. While the estimated frequencies of resistance we found (up to 0.9% of cells) are less than estimated in gulls (up to 5% resistant cells) (9) and aquaculture sediments (up to 15% resistant cells) (25), this study highlights the sheer abundance and diversity of potential AR genes across marine sites.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…However, this greatly expands our knowledge of the diversity of genes responsible for these resistance patterns by linking resistance phenotypes to genotypes and identifying potential novel resistance genes. While the estimated frequencies of resistance we found (up to 0.9% of cells) are less than estimated in gulls (up to 5% resistant cells) (9) and aquaculture sediments (up to 15% resistant cells) (25), this study highlights the sheer abundance and diversity of potential AR genes across marine sites.…”
Section: Discussioncontrasting
confidence: 74%
“…Because nitrofurantoin and sulfadimethoxine are synthetic antibiotics, microbes would not experience these molecules in natural microbe-microbe interactions. Resistant bacteria have been isolated from marine environments in proximity to aquaculture facilities or waterways in proximity to human influence (23,(25)(26)(27). In addition, Port and colleagues (24) showed that frequencies of known antibiotic resistance genes were higher nearshore, so anthropogenic inputs can influence resistance patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Like resistance genes, antibiotics are difficult to remove during water treatment, and some have long half-lives in the environment (219,220), resulting in pollution of both rivers and the ocean (221,222). The use of antibiotics in aquaculture adds these compounds directly into water bodies (223,224), raising local antibiotic concentrations. The environmental and health consequences of contaminating water bodies with antibiotics are of significant concern (225)(226)(227), with calls to monitor and control antibiotic pollution (121,228).…”
Section: Pollution With Selective Agentsmentioning
confidence: 99%
“…The aquaculture industry is recently facing a serious setback due to infectious [23] diseases leading to severe economic loss [24]. Although mortalities have been reported in all stages of life, maximum mortalities in all the cultivated fish species have been reported at larval stages.…”
Section: Discussionmentioning
confidence: 99%